Dimensões jurídicas dos fatores ambientais, sociais e de governança (ASG) no Brasil - Freire, Leonardo Vitor de Paiva (2024)
The Brazilian society has been currently experiencing an increasing demand for products and investments deemed as “sustainable”. Expressions such as green bonds, sustainable financing and especially the term “ESG” – an English acronym for “environment, social and governance” – and its corresponding Portuguese version “ASG” have flooded the market and labeled offers, services and products, including financial ones, expressing, at the same time, multiple meanings, including and mainly the socio-environmental purpose and corporate sophistication to which these products are linked, in a global market valued at trillions of dollars. In effect, as these expressions have, due to those sustainable qualities, the potential to influence decision-making processes, inducing behaviors of groups (consumers, financiers, investors and other interested parties) legally protected and legally regulated economic segments – thus, being able to link offers and contracts – their disclosure to the related public and connection with various products and services require skillful responses from the Law in order to prevent and punish injuries to those parties and communities. However, to date, there is still no clear legal definition for the so-called ESG factors, much less an in-depth examination of their nature and respective legal regime(s) in Brazil, which makes it possible to support regulatory techniques that protect rights and impose duties (as well as consequent responsibilities, in case of violation) inherent to the multiple legal relationships in which ESG factors may affect and formed, on the one hand, by the issuers of assets, products and services considered “sustainable” and, on the other, by the recipients-users of this information. In other words, given the social relevance of the so-called ESG factors, it is necessary to cover them with legal foundations capable of providing legal operators in dealing with the multiple legal repercussions of the topic (read legal dimensions). Thus, based on an interdisciplinary approach between Economics and Law, firstly, without any intention of exhausting the topic, this study will seek to identify (i) the descriptive definition of ESG factors based on the zetetic examination of the different economic-socioenvironmental functions that these factors can take on business management, and (ii) the main legal risks associated with the management of ESG factors in a corporation that claim those legal responses. In a second moment and based on those premises established in the first part of the study, also considering the international regulatory experiences, and the Brazilian constitutional legal framework, this study will present (i) the multiple legal dimensions of ESG factors in Brazil, from a business perspective, and (ii) a proposal to define its concept, nature and legal regime applicable to ESG factors in Brazil, in light of the right to sustainable information. With this, we intend to collaborate in the systematization of Brazilian legal knowledge and, perhaps, in resolving hermeneutic and socio-environmental conflicts